Pengaruh Pengungkapan Islamic Social Reporting, Karakteristik dan Kebijakan Perusahaan terhadap Nilai Perusahaan yang Terdaftar di Jakarta Islamic Index 70 - Rosmiasih Rosmiasih; Ilham Ramadhan Ersyafdi (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2023)
Company value is the assumption that investors are at the level of the company's success in managing resources at the end of the current year which is reflected in the company's stock price. If the share price is higher, it means that the welfare of the shareholders is also getting bigger. This study aims to determine whether company value can be affected by ISR disclosure, company size, sales growth, company age, asset growth, funding policy, dividend policy, debt policy in companies listed in JII 70 for the period 2018-2020. By using purposive sampling technique method, 41 out of 101 companies were selected. The results of the study reveal that firm value can be influenced by company age, funding policy and debt policy. While other variables, namely ISR disclosure, company size, sales growth, asset growth and dividend policy have no effect. This study is expected to increase knowledge and references regarding the value and performance of the company, thereby helping investors to make investment decisions.